TV white spaces maps computation through interference analysis - Dionísio, Rogério Pais (2011)
For the characterization of TV White Spaces (TVWS), an extensive simulation of the impact of interfering signals was undertaken in a generalized scenario. The simulation for these investigations was derived from a Monte Carlo methodology using SEAMCAT, and the results include the computation of TVWS maps as it can be done with the access to a geo-location database, or based on autonomous sensing only. Geo-location database approach is shown to utilize TVWS spectrum more efficiently. The impact of Professional Wireless Microphone Systems (PWMS) devices on the availability of TVWS is also analyzed and imposes additional limitations of the maximum power emitted by secondary spectrum users.